Analisis Pengaruh Electronic Word of Mouth, Brand Image, dan Persepsi Harga terhadap Minat Beli Album Musik Secret Number Dikalangan Penggemar Musik KPop Generasi Z - Ragil Yong Sen Dwi Putra; Endika Perdana (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
K-pop music is currently one of the most popular types of music among Indonesian people, especially Gen-Z, so that the interest in buying music albums among Gen-Z continues to increase along with the increasing influence of digital media and Korean cultural trends in Indonesia. This study aims to determine the effect of electronic word of mouth, brand image, and price perception on the interest in buying Secret Number music albums among Generation Z kpop music fans. The sample of this study amounted to 100 respondents. The sampling technique used was the purposive sampling method. This study uses primary data. The tests carried out include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial t-tests, simultaneous f-tests, and coefficient of determination tests. The results of the study show that the variables of electronic word of mouth, brand image, and price perception influence the interest in buying Secret Number music albums among Generation Z kpop music fans, and the most dominant variable influencing the interest in buying is the price perception variable.